Comparison of CT/MRI-CEUS and US-CEUS fusion imaging techniques in the assessment of the thermal ablation of liver tumors. (31st December 2018) - Xu, Erjiao; Long, Yinglin; Li, Kai; Zeng, Qingjing; Tan, Lei; Luo, Liping; Huang, Qiannan; Zheng, Rongqin
Abstract: Purpose: To compare the applicability of fusion imaging between contrast-enhanced ultrasound (CEUS) and computed tomography (CT) or magnetic resonance imaging (MRI) (CT/MRI-CEUS fusion imaging) and fusion imaging between CEUS and ultrasound (US-CEUS fusion imaging) in the assessment of treatment response during liver cancer ablation. Methods: From August to December 2015, patients who underwent US-guided thermal ablation of liver tumors at our hospital with available CT/MRI images were enrolled consecutively. Both CT/MRI-CEUS and US-CEUS fusion imaging were performed in all patients to evaluate treatment responses. The applicable rate, success rate of registration and duration time were recorded. Complications were monitored in the follow-up period, and CECT/MRI within three months were taken as the standard reference of technical efficacy. Results: A total of 157 liver tumors (19 ± 8 mm, range 8–55 mm) in 115 patients (54 ± 11 years old, range 2 7∼ 84 years old) were enrolled. The applicable rate of US-CEUS fusion imaging was 61.1% (96/157) because of inconspicuous lesions in US, lower than that of CT/MRI-CEUS fusion imaging (99.7% (155/157)) ( p < .05). However, the success rate of registration in US-CEUS fusion imaging (93.8% (90/96)) was superior to that of CT/MRI-US fusion imaging (81.3% (126/155)) ( p < .05), especially for cases combined with alternative preablation surgeries or procedures ( p < .05). The technical efficacy rate was 99.3% (150/151) according to the CECT/CEMRI. Conclusions: Both CT/MRI-CEUS and US-CEUS fusion imaging are feasible means for intraprocedural immediate evaluation of treatment response for liver thermal ablation. US-CEUS fusion imaging is preferred because of its convenience and higher success rate of registration.